Association between PTPN22‐1123G/C and susceptibility to rheumatoid arthritis: A systematic review and meta‐analysis. (7th April 2019) - Wu, Xuangao; Yang, Hye Jeong; Jung Kim, Min; Zhang, Ting; Qiu, Jing Yi; Park, Sunmin
Abstract: Background: The incidence of rheumatoid arthritis (RA) varies greatly among different ethnic groups, suggesting genetic susceptibility. The several genetic variants of protein tyrosine phosphatase, non‐receptor type 22 ( PTPN22 ‐1123G/C, rs2488457) have been widely examined. We systematically evaluated the association of PTPN22 ‐1123 and RA risk by pooling the related studies conducted in different races. Methods: Literature was searched using PubMed, EMBASE, Cochrane Library, Korean scientific database, Chinese medical databases, and the Indian medical database to identify eligible studies for determining the association of PTPN22 ‐1123 and RA risk. The association was assessed in five genetic random effects models including the allelic (AG), recessive (RG), dominant (DG), homozygous (HMG), and heterozygous (HTG) genetic models. Subgroup analyses stratified by ethnicity (Asians and non‐Asians) were assessed. Results: A total of 10 articles were selected that met the criteria including Hardy‐Weinberg equilibrium. Subjects included 14 186 healthy controls and 5735 with RA. The AG, RG, DG, and HMG genetic models showed no heterogeneity, but the HTG model showed heterogeneity. AG and RG did not exhibit publication bias in any of the studies including Asian and non‐Asian subgroups. The overall effect of PTPN22 ‐1123 on RA risk in all genetic random models showed significant positive associations (AG: odds ratio [OR]: 1.24; CI: 1.08‐1.42; P  = 0.002; RG: OR: 1.35; CI: 1.15‐1.59; P  = 0.0003; DG: OR: 1.42; CI: 1.09‐1.85; P  = 0.009; HMG: OR: 1.69; CI: 1.22‐2.34; P  = 0.002). A significant association when pooling the studies was only revealed in non‐Asians ( P  < 0.05), but no significant relationship was shown in Asians. Conclusions: People with C allele in PTPN22 ‐1123 increased the risk of RA only in non‐Asians.